Development, analysis and assessment of solar energy-based multigeneration system with thermoelectric generator - Islam, Shahid; Dincer, Ibrahim; Yilbas, Bekir Sami (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
This study presents comparative energy and exergy analyses of a solar energy based integrated multi-generation system with two unique configurations of thermoelectric generators. System 1 considers an integration of the output of thermoelectric generators with the parabolic solar collectors. In system 2, the thermoelectric generators are incorporated between solar heat exchanger and organic Rankine cycle 1. The heat rejected at low temperature interface of the thermoelectric devices generates electricity through organic Rankine cycle 2. The electricity generated by the thermoelectric generators is used to operate an electrolyzer to produce hydrogen. The utilization of thermoelectric devices developed in system 2 enhances the energy and exergy efficiencies of overall multi-generation system and organic Rankine cycle 1. In addition to this, the net amount of work output by organic Rankine cycle 1 is also improved greatly in system 2. The design configurations of the thermal system and the influences of the operating conditions on the energy and exergy efficiencies of multigeneration/overall system and organic Rankine cycle are investigated. The present results show that an increase in the mass flow rate of solar heat transferring fluid improves the work rate by the turbines and thermoelectric generators appreciably. The proposed system has superior and unique features as compared to the corresponding conventional systems based on thermoelectric generation.
Keywords: Solar energy; Multigeneration; Energy; Exergy; Efficiency; Thermoelectric generators; ORGANIC RANKINE-CYCLE; PERFORMANCE ASSESSMENT; HYDROGEN-PRODUCTION; INTEGRATED-SYSTEM; POWER-GENERATION; THERMODYNAMIC ANALYSIS; HEAT; CONFIGURATIONS; REFRIGERATION; TRIGENERATION; Thermodynamics; Energy & Fuels; Mechanics